UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI SUPERVISI AKADEMIK PADA MASA PANDEMI DI SDN 16 SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - ERMAIDA ERMAIDA (JURNAL ILMIAH SIMANTEK, 2023)
This research is motivated by there are still teachers who have not prepared learning plans in accordance with the conditions of the Covid-19 Pandemic where face-to-face obligations with students are not carried out, so it is adjusted to the learning conditions that can be carried out by students at home and assisted by their parents or guardians. This research was conducted at SDN 16 Sungai Limau. The implementation time is planned for one month starting from October 1 to October 30, 2020. The implementation of actions consists of 2 cycles. The instruments used in this study are: observation sheet. The results showed that continuous academic supervision was scientifically proven to improve teacher competence in compiling syllabus and lesson plans at SDN 16 Sungai Limau. This is evident by the increase in the number of good teacher syllabi from 31% to 87.5% after academic supervision. In addition, the number of good quality RPPs also increased from 25% to 87.5%.